Pengaruh Pengembangan Karir dan Kompensasi Terhadap Kepuasan Kerja Karyawan - Dian Prasetyo Widyaningtyas; Nila Fransiska; Bonaventura Hendrawan Maranata (Journal of Trends Economics and Accounting Research, 2023)
Job satisfaction is a crucial factor to be considered in the management and empowerment of human resources within a company. This research aims to achieve the following objectives: (1) Determine the impact of career development on employee job satisfaction at PT Putmasari Perkasa Semarang. (2) Assess the influence of compensation on employee job satisfaction at PT Putmasari Perkasa Semarang. (3) Examine the combined impact of career development and compensation on employee job satisfaction at PT Putmasari Perkasa Semarang. Descriptive analysis is employed in this research, utilizing the multiple linear analysis method. The SPSS program is utilized for data processing and analysis. A quantitative descriptive research method is applied, where variables are measured using a Likert scale. Data collection involves the distribution of questionnaires to respondents, who are employees of PT Putmasari Perkasa Semarang. The findings of this research indicate that: (1) Career development significantly and positively influences employee job satisfaction at PT Putmasari Perkasa Semarang, with a significance level of 0.000 < 0.05. (2) Compensation also has a positive and significant impact on employee job satisfaction at PT Putmasari Perkasa Semarang, with a significance level of 0.000 < 0.05. (3) The combined influence of career development and compensation significantly affects employee job satisfaction at PT Putmasari Perkasa Semarang, with a significance level of 0.000 < 0.05.